The use of sodium caseinate in the freezing of sheep semen - Salgado, Letícia C. [UNESP]; Codognoto, Viviane M. [UNESP]; Garcia, Rodrigo [UNESP]; Canuto, Lucas E. F. [UNESP]; Denadai, Renan [UNESP]; Freitas-Dell'Aqua, Camila P. [UNESP]; Almeida Filho, Rogério A. [UNESP]; Sitó-Silva, Luan [UNESP]; Crespilho, André M. [UNESP]; Oba, Eunice [UNESP] (Wiley, 2024)
The aim of this study was to assess the addition of 2% sodium caseinate in a commercial egg yolk-based medium in frozen ovine semen. Eight Dorper males were used for the study. The ejaculate was divided into two portions and frozen without (G1) or with the addition of 2% sodium caseinate (G2). Kinetic parameters were evaluated using CASA (computer-assisted sperm analysis), and membrane and acrosome integrity as well as oxidative stress were assessed using flow cytometry. After thawing, a thermoresistance test was conducted at time points T0 and T90. For the fertility test, 100 ewes were inseminated with semen from two rams selected based on in vitro parameters, one with good post-thaw quality (+70% total motility) and the other with low post-thaw quality (−55% total motility). For the fertility test, the females were divided into 4 groups for insemination: low-quality ram without caseinate (GBS = 25) and with caseinate (GBC = 25), and high-quality ram without caseinate (GAS = 25) and with caseinate (GAC = 25). Regarding the results of sperm kinetics, there was a statistically significant difference in the parameters of average path velocity (VAP) and curvilinear velocity (VCL) between the group frozen with BotuBov and the group with added caseinate. At time point T90, straight-line velocity maintained a trend (p <.06), with BotuBov® (BB group) being superior to caseinate this time, and in the linearity parameter, caseinate was superior to BotuBov®. Flow cytometry analysis showed no difference between any of the evaluated tests. In the fertility test, there was no statistically significant difference in the pregnancy rate between the BotuBOV® group (23%, 11/48) and the sodium caseinate group (BC group) (33%, 17/52), and no differences were observed in the male versus diluent interaction (p =.70). In conclusion, sodium caseinate supplementation did not influence sperm kinetic parameters and the fertility of sheep.
Keywords: egg yolk; ram; seminal diluent; spermatozoa